Analisis Pengaruh Kualitas Institusi, Keterbukaan Perdagangan, Inflasi, Ukuran Pasar dan Infrastruktur terhadap Foreign Direct Investment di Negara-Negara ASEAN - Purwono Purwono (Universitas Diponegoro, 2021)
The main problem for any country, especially in developing countries in the process of economic development, is the level of output produced is low as a result of limited capital flows. To be able to increase economic development, one way that can be done is by attracting foreign direct investment. This study aims to analyze the determinants of foreign direct investment (FDI) in terms of institutional and macroeconomic factors in ASEAN countries in the period 2003-2019. This research uses panel data regression analysis method with Fixed Effect Model (FEM) approach. The results of this study show that institutional quality variables such as political stability and the absence of violence/terrorism, government effectiveness have a positive and significant influence on FDI inflows. Then, the control of corruption has a negative and significant effect on FDI inflows. Meanwhile, macroeconomic variables such as trade openness, market size, infrastructure have a positive and significant influence on FDI inflows in ASEAN countries. On the other hand, inflation has a negative and significant effect on FDI inflows. With these results, the quality of institutions and macroeconomic conditions in the ASEAN region plays an important role in attracting FDI inflows.